DECISION SUPPORT AND MONITORING SYSTEMS FOR HUMANITARIAN PROGRAMS USING FORWARD CHAINING METHOD - Purwati, Yuli; Pambudi, Aldi Setia (LPPM Nusa Mandiri, 2022)
One of the covid-19 pandemic impacts is the emergence of new social problems. Humanitarian agencies are helping the government's role to overcome various social issues that arise through its humanitarian programs. One of which is with the MSR program from Aksi Cepat Tanggap Purwokerto. With increasing social problems and the complexity of improving data collection due to the covid-19 pandemic, the methods' limitations previously using paper will be difficult, and the limits of people who have the expertise to make decisions related to the submission of prospective beneficiaries. A decision support system is needed to provide suggestions of results under the rules that have will determining and monitoring and filing systems to provide convenience in managing data collection.